A RARE CLINICAL PRESENTATION: A PATIENT WITH CHRONIC RENAL FAILURE, SECONDARY HYPERPARATHYROIDISM AND CALCIPHYLAXIS - Celik, M. (Acta Endocrinol (Buchar), 2016)
Calciphylaxis, also known as calcific uremic arteriolopathy (CUA), is usually observed in women and it is a serious complication of hyperparathyroidism secondary to chronic renal failure. CUA is characterized by ischemic tissue loss secondary to progressive vascular degeneration. Although it is rare, it may end up with sepsis and organ failure and can be fatal. Its pathogenesis is not fully understood, but it is thought that it occurs secondary to increased calcification activators such as oxidized LDL, TNF- α, calcitriol, fibronectin, collagen-I, and TGF-1α. The most effective treatment is managing underlying pathology and decreasing serum calcium and phosphorus levels. In this report, we aimed to present an end stage renal failure case with coexisting hyperparathyroidism, hyperthyroidism and calciphylaxis in whom cutaneous manifestations were healed 6 months after parathyroidectomy.